Hair cortisol as outcome parameter for psychological and neuropsychiatric interventions—a literature review - Botschek, Tim; Hußlein, Vincent; Peters, Eva M. J.; Brosig, Burkhard (Frontiers in Psychiatry, 2023)
Background: Studies measuring hair cortisol concentration (HCC) have been increasingly conducted to document stress-related, endocrine changes aggregated over time. Previous studies have shown that HCC reflects abnormalities in the hypothalamic-pituitary-adrenocortical axis (HPA axis) in the context of somatic diseases, such as Cushing's syndrome. HCC variations also reveal a corresponding alteration in HPA-axis-function in mental disorders, highlighting its potential role as a biomarker for interventions targeting mental health problems. Aims: The aim of this study was to investigate the role of HCC in various psychological and neuropsychiatric interventions and to explore the extent to which HCC can serve as a predictive or outcome parameter in such interventions by conducting a PRISMA-compliant review of the literature. Methods: From May to July 2022, the databases Web of Science, Google Scholar, PsychINFO and ResearchGate were systematically searched using different combinations of relevant keywords. Studies of different types that examined HCC in the context of a wide range of psychological and neuropsychiatric interventions were included. Studies in languages other than English or German and animal studies were excluded. The MMAT tool was used, to assesses the Risk of bias. Results: The initial search identified 334 studies. After applying the inclusion and exclusion criteria, 14 publications with a total number of 1916 participants were identified. An association between HCC and PTSD, depressive disorders, and ongoing social and family stress can be documented. The effect of relaxation techniques, mental training, CBT, or PTSD therapy on HCC has been studied with equivocal results. Some studies found decreased HCC after treatment, while others did not show a clear effect. Baseline HCC appears to be of particular importance. In some studies, higher baseline HCC was associated with increased treatment response, providing a predictive value for HCC. Discussion: HCC is increasingly being used as a biomarker for the mapping of psychological and neuropsychiatric interventions. However, due to the wide range of study populations and interventions, results are still heterogeneous. Nevertheless, HCC seems to be an encouraging biological parameter to describe the trajectory of different interventions aimed at improving mental health.